2009
DOI: 10.1016/j.ijsolstr.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mixed-mode stress intensity factors for nonhomogeneous materials using an interaction integral method

Abstract: a b s t r a c tAn interaction (energy) integral is derived for the computation of mixed-mode stress intensity factors (SIFs) in nonhomogeneous materials with continuous or discontinuous properties. This method is based on a conservation integral that relies on two admissible mechanical states (actual and auxiliary fields). In general, the interaction energy contour integral is converted into an equivalent domain integral in numerical computations. It can be seen from the equivalent domain integral, the integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 51 publications
(55 reference statements)
4
46
1
Order By: Relevance
“…Such a case study was reported earlier in [74]. The observations in the SIF variation, for both the cases, are consistent with the results of reference [58]. The crack opening displacement ( COD v ) profiles, obtained using the proposed EFG method and FEM are compared in Fig.…”
Section: Orthogonal Crack Near Materials Interfacesupporting
confidence: 88%
See 2 more Smart Citations
“…Such a case study was reported earlier in [74]. The observations in the SIF variation, for both the cases, are consistent with the results of reference [58]. The crack opening displacement ( COD v ) profiles, obtained using the proposed EFG method and FEM are compared in Fig.…”
Section: Orthogonal Crack Near Materials Interfacesupporting
confidence: 88%
“…The same interaction integral is also used to extract the T-stress with the help of different auxiliary functions [57]. A modified interaction integral [58] is used to extract mixed-mode SIFs for a crack when it is close to material interfaces.…”
Section: Interaction Integral To Extract Sifs and T-stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The interested reader is referred to the review paper on stress intensity factor calculations within an XFE framework [43]. An important adaptation to the interaction integral was introduced in [44] for non-homogeneous, isotropic materials with arbitrarily continuous properties. This approach takes account of the difference in material properties between the crack tip and the Gauss points contained within the J-domain.…”
Section: The Interaction Integral For Sif Evaluationmentioning
confidence: 99%
“…It has been found that the J-integral and its related techniques play an important role in static fracture mechanics, which can be referenced to the article written by Yu et al [1]. In the case of dynamic fracture mechanics, Kishimoto et al [2] developed a modified J-integral, which involves the inertial effects to determine DSIFs in conjunction with the finite element method (FEM).…”
Section: Introductionmentioning
confidence: 99%